Analisis Nilai Karakter Film”Battle of Surabaya” Sebagai Media Pembelajaran PPKn Kelas 6 Sekolah Dasar - Alfan Setiyawan; Hamidaturrohmah, Hamidaturrohmah; Nina Sofiana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The teacher's challenge in implementing character education in elementary schools is increasingly complex. Planting character requires the right way so that it can be internalized in students so that it can become a habit. This study aims to analyze the value of the characters in the film